2019
DOI: 10.25053/redufor.v4i11.254
|View full text |Cite
|
Sign up to set email alerts
|

As tecnologias de informação e comunicação na formação inicial de professores do 1º ciclo do ensino básico – fatores constrangedores invocados pelos formadores para o uso das tecnologias

Abstract: O artigo apresenta os resultados de uma investigação que se materializa no campo das práticas de formação inicial de professores do 1.º ciclo do ensino básico. Pretende dar a conhecer as representações sobre os fatores que atuam como barreira ao uso e promoção das tecnologias de informação e comunicação (TIC) na preparação profissional dos futuros professores para o uso pedagógico das TIC. É um estudo descritivo interpretativo, centrado nos formadores de duas instituições públicas de Ensino Superior em Portuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
5
0
5
Order By: Relevance
“…state that a teacher with a high sense of self-efficacy presents himself as a proactive teacher, who believes in the existence of the necessary external and internal resources, who takes responsibility for his own professional growth, who focuses on the search for solutions to problems, regardless of the causes that originate them, who choose their paths of action and that creates meaning and sense for their lives by setting ambitious personal goals.More recent research shows that contextual factors such as teaching resources, support from colleagues, and mediated experiences influence pre-service teachers' self-efficacy and beliefs (TSCHANNEN-MORAN; HOY 2007). Some studies developed around the concept, and within the scope of Social cognitive theory, have shown that the level of teacher self-efficacy appears strongly correlated with the willingness to adopt new practices and methodologies in the classroom (KAGIMA; HAUSAFUS, 2000; SMYLIE, 1998).The teachers' self-efficacy and confidence were referred in many studies as important factors to promote the use of digital technologies in education(FONSECA, 2019; PEDRO; PIEDADE, 2013; PIEDADE; PEDRO, 2014) and, in particular the use of educational robotics(JAIPAL-JAMENI;ANGELI, 2017;LEONARD et al, 2018;GÜNBATAR, 2019). Jaipal-Jamani and Angeli (2017) andLeonard et al (2018) reported the positive effects of robotics on pre-service teachers' self-efficacy, science learning, and computational thinking knowledge.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…state that a teacher with a high sense of self-efficacy presents himself as a proactive teacher, who believes in the existence of the necessary external and internal resources, who takes responsibility for his own professional growth, who focuses on the search for solutions to problems, regardless of the causes that originate them, who choose their paths of action and that creates meaning and sense for their lives by setting ambitious personal goals.More recent research shows that contextual factors such as teaching resources, support from colleagues, and mediated experiences influence pre-service teachers' self-efficacy and beliefs (TSCHANNEN-MORAN; HOY 2007). Some studies developed around the concept, and within the scope of Social cognitive theory, have shown that the level of teacher self-efficacy appears strongly correlated with the willingness to adopt new practices and methodologies in the classroom (KAGIMA; HAUSAFUS, 2000; SMYLIE, 1998).The teachers' self-efficacy and confidence were referred in many studies as important factors to promote the use of digital technologies in education(FONSECA, 2019; PEDRO; PIEDADE, 2013; PIEDADE; PEDRO, 2014) and, in particular the use of educational robotics(JAIPAL-JAMENI;ANGELI, 2017;LEONARD et al, 2018;GÜNBATAR, 2019). Jaipal-Jamani and Angeli (2017) andLeonard et al (2018) reported the positive effects of robotics on pre-service teachers' self-efficacy, science learning, and computational thinking knowledge.…”
mentioning
confidence: 99%
“…Jaipal-Jamani and Angeli (2017) andLeonard et al (2018) reported the positive effects of robotics on pre-service teachers' self-efficacy, science learning, and computational thinking knowledge. Thus, the initial teacher training programs are the right place to develop the future teacher self-efficacy(CARDOSO, 2016;FONSECA, 2019).…”
mentioning
confidence: 99%
“…Other studies indicate that some teachers' insecurities and fears in using ICT restrict their willingness to try them out [38], and that teachers with low ICT integration, report lower confidence in using computers [39]. According to ref.…”
Section: Teacher's Self-efficacymentioning
confidence: 99%
“…O acesso à internet expandiu as possibilidades de interação e, por conseguinte de colaboração entre as pessoas. Laru, Näykki e Jäverlä (2015), Berribili e Mill (2018), Fonseca (2019), reforçam que a interação entre as atividades individuais e colaborativas estão estabelecendo novos desafios para apoiar o ensino. Para isso, é necessário pensar como os docentes podem integrar estas tecnologias aos métodos mais ou menos tradicionais de ensino e currículo.…”
Section: Mobile Collaborative Learning E O Ensino De Ciênciasunclassified